2015
DOI: 10.1128/jvi.01517-15
|View full text |Cite
|
Sign up to set email alerts
|

L Particles Transmit Viral Proteins from Herpes Simplex Virus 1-Infected Mature Dendritic Cells to Uninfected Bystander Cells, Inducing CD83 Downmodulation

Abstract: Mature dendritic cells (mDCs) are known as the most potent antigen-presenting cells (APCs) since they are also able to prime/ induce naive T cells. Thus, mDCs play a pivotal role during the induction of antiviral immune responses. Remarkably, the cell surface molecule CD83, which was shown to have costimulatory properties, is targeted by herpes simplex virus 1 (HSV-1) for viral immune escape. Infection of mDCs with HSV-1 results in downmodulation of CD83, resulting in reduced T cell stimulation. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 60 publications
0
51
0
Order By: Relevance
“…Within the tripartite gene expression cascade of HSV-1, the immediate early gene product infected cell protein 0 (ICP0) was proven to be essential and sufficient to induce the proteasome-dependent, but ubiquitin-independent, CD83 degradation in mDCs (76). Besides the loss of CD83 protein expression on directly HSV-1-infected mDCs, it has been reported that uninfected bystander mDCs also display a severe reduction of CD83 (77). This bystander effect was attributed to so-called L-particles, which are released by infected cells upon an HSV-1 infection and are non-infectious themselves, due to the lack of the DNA-containing capsid.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Within the tripartite gene expression cascade of HSV-1, the immediate early gene product infected cell protein 0 (ICP0) was proven to be essential and sufficient to induce the proteasome-dependent, but ubiquitin-independent, CD83 degradation in mDCs (76). Besides the loss of CD83 protein expression on directly HSV-1-infected mDCs, it has been reported that uninfected bystander mDCs also display a severe reduction of CD83 (77). This bystander effect was attributed to so-called L-particles, which are released by infected cells upon an HSV-1 infection and are non-infectious themselves, due to the lack of the DNA-containing capsid.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…The plates were incubated in darkness for 15 min at 25°C. The reaction was stopped with 2 M H 2 SO 4 , and the absorbance was measured at 450 nm using a microplate absorbance reader (BioTec, USA) (65,66).…”
Section: Fig 10mentioning
confidence: 99%
“…have also shown that L-particles are able to facilitate HSV-1 infection (13, 53) by enhancing virus replication and impairing the host immune response (52,54). However, no systematic analysis of the protein and RNA compositions of HSV-1 L-particles, or the cellular response from targeted cells, has been carried out.…”
Section: Discussionmentioning
confidence: 99%